Evaluation of Bamboo Paper Properties by Blending Recycled Pulp and Starch - PETERUS, JASON USUNG (Progress in Engineering Application and Technology, 2023)
The aims of this study is to determine the change of bamboo paper when blending with recycle paper and addition of cationic starch (CS) as the dry strength additives (DSA). Two type of condition be evaluate in determine the structure and mechanical properties of the paper. Four type of doses that include 100%, 90%, 80% and 70% of recycle and 10%, 20% and 30% of Bamboo pulp. The experiment in preparing the paper and paper testing base on the TAPPI and MS ISO standards. The increasing of the paper strength significant in the tearing test for 70% recycle paper with 1.5% CS at . In the busting and tensile testing, the result is not significant between both condition. In the the Morphonology of the surface, DSA paper structure well in decreasing the pores on the paper surface.